2015
DOI: 10.2174/1871530315666150907111120
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Lipid Profile in HIV-Infected Adults

Abstract: In the last decades, there have been many reports of HIV infection and abnormalities in lipid metabolism and cardiovascular disease (CVD). This study aims at describing the nutritional status of HIV-infected adults and its relation to lipid profile through traditional [total cholesterol (TC), HDL cholesterol (HDL), triglycerides (TG), non-HDL cholesterol and LDL cholesterol (LDL)] and other parameters [Apolipoprotein B (ApoB), fibrinogen, and high sensitive-C-reactive protein (hs-CRP)]. A cross-sectional descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The development of comorbid disease in HIV-infected persons is believed to have both traditional and HIV-/ART-specific contributors: Obesity, and particularly VAT accumulation, are associated with systemic[12, 47] and adipose tissue inflammation[48], insulin resistance, dyslipidemia[49] and increased oxidative stress[50]. At the same time, adipose tissue is a potential HIV reservoir, leading to recruitment of T lymphocytes and macrophages into adipose tissue.…”
Section: Consequences Of Obesity and Visceral Adipositymentioning
confidence: 99%
“…The development of comorbid disease in HIV-infected persons is believed to have both traditional and HIV-/ART-specific contributors: Obesity, and particularly VAT accumulation, are associated with systemic[12, 47] and adipose tissue inflammation[48], insulin resistance, dyslipidemia[49] and increased oxidative stress[50]. At the same time, adipose tissue is a potential HIV reservoir, leading to recruitment of T lymphocytes and macrophages into adipose tissue.…”
Section: Consequences Of Obesity and Visceral Adipositymentioning
confidence: 99%
“…Obesity likely has similar metabolic and inflammatory consequences in HIV-infected persons as in the general population (Figure 1). Obesity and lipohypertrophy, particularly VAT accumulation, are often associated with chronic inflammation in adipose tissue, insulin resistance [51][52][53][54], increased metabolic syndrome risk [55], dyslipidemia [56] and increased oxidative stress [57]; abdominal obesity is robustly associated with cardiovascular disease (CVD) risk and mortality [58][59][60]. However, for any given BMI, HIV infection appears to confer greater Poorer neurocognitive function was associated with increased waist circumference (WC) among HIV-infected participants in the CHARTER study [25].…”
Section: Consequences Of Obesity and Lipohypertrophymentioning
confidence: 99%
“…In agreement with studies that demonstrated an increasing prevalence of obesity among PWH, 13 we observed increased adiposity measured by standard BMI criteria (ie, BMI $ 25 kg/m 2 ) and waist circumference, which are associated with numerous metabolic and inflammatory effects among PWH, having implications for morbidity and mortality. [29][30][31][32] The relationship between abdominal adiposity and adipokines may be exacerbated in PWH because ART toxicity can alter the hemostatic regulation of adipokines. 33 In our study, increased abdominal adiposity was associated with higher levels of hsCRP, which appears central in both adiposity-and sarcopenia-associated inflammation.…”
Section: Discussionmentioning
confidence: 99%